PRESISI DAN AKURASI HASIL PENELITIAN KUANTITATIF BERDASARKAN PENGAMBILAN SAMPEL SECARA ACAK - Didik Sumanto (JURNAL LITBANG, 2005)
Sampling technique that has the highest precision in this research is the stratified random sampling technique. The variance of this sampling technique is only 0.132 meanwhile those of the simple random sampling and cluster random sampling techniques are 0.260 and 3.012 respectively. By using the sanpling error formula we can obtain the smallest sampling error on the simple random sampling of  0.0125, while for the stratified random sampling technique and cluster random sampling technique, the sampling error are 0.0203 and 0.0302 respectively. If the accuracy is seen from the extent of bias obtained from each sampling technique against the parameter value, the stratified random sampling technique has the highest accuracy because it has bias of just 0.295433 while the simple random sampling technique and the cluster random sampling technique have the bias of 0.403317 and 1.502863 respectively. The data collection using the three random sampling techniques in this research in fact gives no significant difference of level of skills. On the statistical test of Kruskal- Wallis by using EPI Info Program of version 6.0, it is obtained that p value is 0.889212 on the sampling error of 5%. Meanwhile the statistic testing against the amount of bias on the three random sampling techniques, it is obtained that the p value is 0.001006. The significant difference is obtained from the extent of bias from the three sampling technique with the sampling error of 5 % Key words: precision, accurac)4 random sampling technique